Analisis Kesesuaian Materi Ajar Blok Tropical Medicine Tahun Ajaran 2016/2017 Fakultas Kedokteran Universitas HKBP Nommensen Medan - Jenny Novina Sitepu (Nommensen Journal of Medicine, 2019)
Learning method and learning content must be suitable with Learning objectives in the ideal curriculum. Standar Kompetensi Dokter Indonesia (SKDI) 2012 as a minimal competency standard that any doctor in Indonesia able to do. The aim of this study was to evaluated the suitability of learning content with learning objectives and SKDI 2012 in Tropical Medicine Modules Educational Year 2016/2017 Medical Faculty of Universitas HKBP Nommensen. This study was a qualitative descriptive study with documents analysis design. The documents that have been analysed were module learning objectives which described in buku rencana pengajaran, satuan acara perkuliahan, practical guidelines, tutorial guidelines, skills lab guidelines and student examination scores. The suitability of variables were evaluated by evaluation rubric that have been arranged before. Every learning objective has been described in learning content, although a learning objective could not described in every learning method. Tetanus and difteria were not described in learning content although they were included in SKDI 2012. Teaching materials given to students in general are in accordance with the learning objectives and SKDI in 2012.